Management of Ecology-Based Tourism Resources in Tarabunga Village and Lumban Silintong, Toba Samosir Regency - OslandHerijon Lingga (Akademi Pariwisata Darma Agung, 2021)
The management of tourism resources illustrates an important element to be taken into account for conventional tourism development which tends to be exploitative and ignores the carrying capacity of the physical and social environment. Because the development of the tourism industry is obliged to maintain the quality of the environment, maintaining the noble heritage of local cultural traditions which is useful for increasing economic growth. If the manager of tourism resources is ignored and not managed properly, the process of destruction of nature and traditional values ​​will occur more quickly and will have an impact on the sustainability of the tourism ecosystem in Tobasa district. What is the condition of the tourism resource managers in Tarabunga and Lumban Silintong Villages, Tobasa Regency, is the tourism resource management in Tarabunga and Lumban Silintong Villages, Tobasa Regency following the principles of sustainable tourism. The paradigm shift from production-centered development to people-centered development has implications for the emergence of new management, known as Local Resource Management (PSDL) or community based resource management. This new development management has changed the role of government bureaucracy to create conditions that give people the ability to develop themselves. This study analyzes ecology-based tourism resource management using descriptive methods by analyzing data qualitatively. This method is used to collect data and information about local situations and conditions based on accurate facts. The management of tourism resources in Tarabunga and Lumban Silintong Villages in Tobasa District has not been integral because it does not involve local communities. The local community as the host is placed in a position outside the management system. Less attention to sustainable principles in preserving the environment, nature and local culture which results in disharmony of nature. Institutional functions that do not yet exist also involve the surrounding community which is still very minimal and also some aspects that are still not good, such as accessibility and management of the physical environment which still tends to be neglected.